Adaptive Management: Learning and Action Approaches to Implementing Norms-shifting Interventions - McLarnon, Courtney; Gayles, Jennifer; Deepan, Prabu (USAID / Passages, 2021)
What Passages has Learned about Adaptive Management: • Be reflective about information that is collected and create a culture of learning. • Be systematic about establishing monitoring and learning systems. • Be strategic about data sources and analysis, prioritizing areas for learning and addressing issues raised. • Be inclusive about information collection: who is collecting what, how, and how is it being used.

Building a team culture for Adaptive Management in MSD: 5 Strategies MEL Managers Say Work - Gover, Dun; Nasution, Zulka; Okutu, David; Bolder, Meghan; Henao, Lina (MSD in MEL Brief, 2023)
Keywords: Bolder Meghan; Gover Dun; Henao Lina; Nasution Zulka; Okutu David

Collaborating, Learning, and Adapting Framework & Key Concepts (Implementing Partner Version 1) - USAID LEARN (USAID, 2022)
Although collaborating, learning, and adapting (CLA) are not new to USAID and its implementing partners, they often do not happen regularly or systematically and are not intentionally resourced. The CLA Framework above identifies components and subcomponents to help you think more deliberately about what approach to CLA might be best tailored to your organizational or project context. The framework recognizes the diversity of what CLA can look like in various organizations and projects while also giving CLA structure, clarity, and coherence across two key dimensions: - CLA in the Program Cycle: how CLA is incorporated into planning and design processes throughout the Program Cycle in order to improve their effectiveness; and - Enabling Conditions: how an organization’s culture, daily operating processes, and resource allocation support CLA integration. Organizations need both integrated CLA practices appropriate for their context and conducive enabling conditions to become stronger learning organizations capable of managing adaptively. The framework stresses the holistic and integrated nature of the various components of CLA to reinforce the principle that CLA is not a separate workstream—it should be integrated into existing processes to strengthen the discipline of development and improve aid effectiveness.

Local Systems Position Paper - USAID (USAID, 2024)
The Local Systems Position Paper describes the key approaches USAID will use to translate systems thinking into systems practice. It focuses on ways USAID can better understand and engage local systems to support them in producing more sustainable results. Systems thinking is a mindset and set of tools that we use to understand how systems behave and produce certain results or outcomes. Systems practice is the application of systems thinking to better understand challenges and strengthen the capacity of local systems to unlock locally led, sustained progress. The shift from systems thinking to systems practice is driven by a desire to integrate systems practice throughout the Program Cycle and increase our capacity to actively and adaptively manage programming in ways that recognize complexity and help make our programs more effective and sustainable. These approaches will be utilized alongside and within the context of USAID’s policies and guidance, including technical guidance for specific sectors, as well as evidence and lessons learned from partners around the world. Systems thinking is a long-standing discipline that can serve as a powerful tool for understanding and working with local systems. It has been a consistent component of USAID’s decades-long commitment to locally led development and humanitarian assistance. USAID uses systems thinking to better understand the complex and interrelated challenges we confront – from climate change to migration to governance – and the perspectives of diverse stakeholders on these issues. When we understand challenges as complex systems – where outcomes emerge from the interactions and relationships between actors and elements in that system – we can leverage and help strengthen the local capacities and relationships that will ultimately drive sustainable progress. Recognizing this, in 2014, USAID released the Local Systems Framework, outlining ten principles to help USAID staff, partners, and local stakeholders place local systems at the center of all of our efforts to promote sustainability. Since then, development and humanitarian actors have embraced systems thinking as a concept and reiterated its importance in other policies, strategies, and tools, across sectors and regions. When USAID released its Localization Vision and Approach in 2022, it included local systems practice as a core component of adapting policies and program practices. Building on the success of the Local Systems Framework, this position paper reiterates USAID’s commitment to systems practice and presents six approaches that will help USAID strengthen and further embed systems practice in all of our work

Enhancing partner and system-level learning: 8 Tips from MEL Managers - Gover, Dun; Nasution, Zulka; Okutu, David; Bolder, Meghan; Henao, Lina (MSD in MEL Brief, 2023)
Effective learning is a key driver of market systems change, with the potential to enhance system competitiveness, resilience, and inclusiveness. Shifting the Locus of Learning: Catalyzing Private Sector Learning to Drive Systemic Change recently outlined a rationale for enhancing the scale and quality of learning in a system and identifying 10 strategies programs can contextualize to catalyze learning. These strategies are also backed with robust examples from 13 programs doing this work across 11 countries. To deepen insights on what MSD Monitoring, Evaluation and Learning (MEL) Managers have experienced in putting several of those strategies into practice, the Feed the Future Market Systems and Partnerships (MSP) Activity convened a series of peer discussions as part of a larger initiative (see Figure 1). This brief shares the collective learning and experience on this topic of three senior MEL Managers who were interested in and had experience with this topic. The group represented full-time, program-based MEL Leads working on MSD programs funded by USAID and DFAT, based in Fiji, Albania, and Kosovo working for Adam Smith International, SwissContact, and DT Global, respectively. From those discussions, this paper synthesizes eight tips from MEL Managers for practically enhancing partner and system-level learning: 1. Identify the right decision-maker(s) at potential partners. 2. Use a co-creation process to identify learning opportunities. 3. Use diagnostics and assessments to strengthen partner and system capacity for actionable learning. 4. Use a phased capacity strengthening process tied to behavior change. 5. Measure partners’ continued investment in and use of learning—not the continuation of specific learning activities. 6. Work with sector-level institutions for scale but be aware of risks. 7. Leverage informal communities of practice to share learning. 8. Use the right terminology to talk about partner and system-focused learning.

Technically Strong and Politically Savvy: Enhancing Thinking and Working Politically when practicing the consevation standards at USAID - Schuttenberg, H.Z.; Stark, J.; Schueler, K. (USAID, 2026)
This supplemental guide offers practical advice for thinking and working politically (TWP) when practicing the Conservation Standards. The CS are a widely used, systematic approach for planning, monitoring, and adapting programs aiming to conserve biodiversity. TWP is an approach to international development that brings greater attunement to the political dynamics of the local programming context in order to enhance development results. Given strong evidence that political factors overwhelmingly drive the loss of biodiversity, this guide is based on the premise that conservation programs will be more effective when they skillfully integrate TWP.

Integrated Governance: Achieving Governance Results and Contributing to Sector Outcomes - Frazer, Sarah; Granius, Mark; Brinkerhoff, Derick W.; McGregor, Lisa (RTI Press Publication, 2022)
Achieving broad-based socio-economic development requires interventions that bridge disciplines, strategies, and stakeholders. Effective sustained progress requires more than simply an accumulation of sector projects, and poverty reduction, individual wellbeing, community development, and societal advancement do not fall neatly into sectoral categories. However, researchers and practitioners recognize key operational challenges to achieving effective integration that stem from the structures and processes associated with the current practice of international development. Integration calls for the intentional linking of intervention designs, implementation, and evaluation across sectors and disciplines to achieve mutually reinforcing outcomes. In this report, we summarize the results of a study we conducted to explore the challenges facing governance programs that integrate with sector interventions to achieve governance outcomes and contribute to sector outcomes. Through a review of policy documents and project reports from recent integrated governance programs and interviews with donor and practitioner staff, we found three integrated governance programming variants, an emphasis on citizen and government collaboration to improve service delivery, interventions that serve as the glue between sectors, and a balancing act for indicators to measure contribution to sectoral outcomes. Our analysis identified four key success factors: contextual readiness, the application of learning and adapting approaches, donor support, and recognition of the limitations of integrated governance. We then discuss recommendations and implications and for answering the challenge of integrating governance and sector programming to achieve development outcomes.

LEARN End of Contract Report - Learning Lab (USAID, 2020)
In September of 2014, USAID’s Office of Learning, Evaluation & Research (LER) awarded the Learning and Knowledge Management (LEARN) contract to Dexis Consulting Group and subcontractor RTI International.1 This document—the End of Contract Report—captures five and half years of results and reflections for our stakeholders. Our intention is to share the good and the bad, and while this report would not be considered a “tell all,” we think we have a story worth sharing, particularly to USAID CORs and AORs, activity managers, and other implementers of institutional support contracts.2 LEARN’s primary purpose was to support organizational change at USAID. More specifically, the contract was focused on helping USAID staff integrate collaborating, learning, and adapting (CLA) approaches into the design, implementation, monitoring, and evaluation of programs (what is known at USAID as the Program Cycle). It was clear that most USAID staff, whether they realized it or not, were already integrating CLA into their work to some extent. The focus of our efforts, therefore, was to make those practices more systematic, intentional, resourced, and ultimately more widespread throughout the Agency, which would have a ripple effect on implementing partners and even other stakeholders, such as host country governments. This was based on the theory—later borne out by evidence—that by becoming a better learning organization, USAID could be a more effective development organization. And that theory brought the USAID CLA team within USAID’s Bureau for Policy, Planning & Learning (PPL) and LEARN contractors together, driven by a shared purpose of improving how USAID does business. LEARN was designed based on this belief and, as you might expect from a learning-oriented contract, began with more questions than answers. Primary among those questions was: could an institutional support contract do more than carry out requested services—could it actually accelerate positive organizational change at USAID? And if so, how and under what conditions?

A Systems Framework for International Development: The Data-Layered Causal Loop Diagram - Blair, Courtney; Gralla, Erica; Wetmore, Finley; Goentzel, Jarrod; Peters, Megan (Production and Operations Management, 2021)
Meeting the United Nations Sustainable Development Goals (SDGs) will require adapting or redirecting a variety of very complex global and local human systems. It is essential that development scholars and practitioners have tools to understand the dynamics of these systems and the key drivers of their behavior, such as barriers to progress and leverage points for driving sustainable change. System dynamics tools are well suited to address this challenge, but they must first be adapted for the data-poor and fragmented environment of development work. Our key contribution is to extend the causal loop diagram (CLD) with a data layer that describes the status of and change in each variable based on available data. By testing dynamic hypotheses against the system's actual behavior, it enables analysis of a system's dynamics and behavioral drivers without simulation. The data-layered CLD was developed through a 4-year engagement with USAID/Uganda. Its contributions are illustrated through an application to agricultural financing in Uganda. Our analysis identified a lack of demand for agricultural loans as a major barrier to broadening agricultural financing, partially refuting an existing hypothesis that access to credit was the main constraint. Our work extends system dynamics theory to meet the challenges of this practice environment, enabling analysis of the complex dynamics that are crucial to achieving the SDGs.